FUNCTIONAL RECEPTION OF THE QUR'AN IN FUNERAL RITUALS: RECITATION OF FOUR SELECTED SURAH IN KAMPUNG TENGAH COMMUNITY, ENOK DISTRICT - Ma’mum, Nurcholish; Wahidi, Ridhoul; Amaruddin, Amaruddin; Murni, Dewi (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2024)
This article examines the diverse public receptions towards the tradition of reciting four selected surahs—Surah Yāsīn, Surah As-Sajdah, Surah Al-Wāqi'ah, and Surah Al-Mulk—during the burial ceremony in Kampung Tengah, Enok Village, Enok District, as a form of practicing the Qur'an in everyday life. Qur'anic studies encompass not only its meaning and interpretation but also the re-actualization of its guidance in societal practices, including traditions and customs. This study aims to describe the reception of the Kampung Tengah community regarding the practice of these four selected surahs in local funeral ceremonies. Using qualitative methods and a living Qur'an approach, this study focuses on describing community receptions of local traditions or social phenomena. The research identifies three key findings. First, the socio-anthropological aspect: this tradition represents a habitual practice among Kampung Tengah residents in conducting burials, including the recitation of these surahs as an expression of solidarity among Muslims. Second, the socio-historical aspect: the tradition originated as a local custom initiated by a Bugis scholar, H. Dullah bin H. Ismail, based on the teachings of Tuan Guru Abdurrahman Shiddiq Al-Banjari in the book Perukunan. Third, the spiritual aspect: the community believes that reciting these surahs brings various virtues (fadhilah) for both the deceased and the living. This article contributes to understanding the relevance of local traditions within Islamic teachings and offers an academic contribution to Qur'anic interpretation studies, particularly the living Qur'an field.